PACE, performance targets and legal protections - Kemp, Vicky (Sweet and Maxwell, 2014)
Managerial influences in the criminal justice system have become increasingly dominant over recent years. There has also been a drift towards summary justice, with the police formally dealing with a significant proportion of cases out-of-court. In this study of four large police stations, performance targets were seen to influence policing strategies and decision-making. Even when performance targets have changed or been eliminated, they can have an enduring effect on relationships and decisions made in police custody. For example, when under pressure to prioritise police performance targets, this encouraged senior officers to intervene in custody decisions, which legislation requires to be made by impartial and independent custody officers. An unintended consequence of performance management, therefore, is the potential to undermine the legal protections of those held in police custody.